A basin‐scale application of environmental DNA assessment for rare endemic species and closely related exotic species in rivers: a case study of giant salamanders in Japan. Issue 2 (13th February 2015) - Fukumoto, Sou; Ushimaru, Atushi; Minamoto, Toshifumi; Crispo, Erika
Summary To prevent the invasion of exotic species causing a decline in an endangered endemic species, it is important to determine the distribution of both species at an early stage, when the density of the exotic species is still low, and to manage the invasion immediately. However, distinguishing between closely related species is difficult because they share similar characteristics. The identification of DNA fragments sampled from a body of water (environmental DNA) has become a popular technique for rapidly determining the distribution of a target species. In this study, we analysed environmental DNA in water samples from 37 sites across the Katsura River basin in Japan. We used TaqMan real‐time PCR to distinguish the Japanese giant salamander Andrias japonicus from the closely related Chinese giant salamander Andrias davidianus, which is known to invade Japanese rivers and hybridize with the Japanese species. In environmental samples, we detected mtDNA of the endemic species at 25 sites and mtDNA of the exotic species at nine sites. The DNA detection sites were concentrated in the upstream region. The exotic species DNA was found beyond the limits of an earlier capturing survey. Synthesis and applications. Using environmental DNA to monitor the two salamander species requires less time and effort than traditional surveys, so a wide‐ranging survey can be conducted rapidly. Our results showed that performing three environmental DNA surveys for each site between autumn and winter is desirable for giant salamanders. Further collection of environmental DNA, in combination with conventional population surveys, will provide valuable information that can help protect rare endemic species in a variety of aquatic ecosystems and can help monitor the invasion of exotic species.